2020
DOI: 10.3389/fcell.2020.587389
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Ubiquitin Specific Peptidase 13 Contributes to Tumor Growth and Metastasis via Enhancing the Toll-Like Receptor 4/Myeloid Differentiation Primary Response Gene 88/Nuclear Factor-κB Pathway in Hepatocellular Carcinoma

Abstract: Gao et al. USP13/TLR4 Axis in HCC Progression knockdown repressed hypoxia-induced activation of the TLR4/MyD88/NF-κB pathway in HCC cells. In conclusion, our study uncovered that hypoxia-induced USP13 facilitated HCC progression via enhancing TLR4 deubiquitination and subsequently activating the TLR4/MyD88/NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…To date, no less than 100 genes that encode DUBs have been identified in the human genome. Several studies have confirmed that DUBs play essential roles in the occurrence and progression of human cancers, and have thus provided emerging drug discovery opportunities [9][10][11][12]. In GC, several DUBs participate in tumor initiation and progression.…”
Section: Ivyspring International Publishermentioning
confidence: 94%
“…To date, no less than 100 genes that encode DUBs have been identified in the human genome. Several studies have confirmed that DUBs play essential roles in the occurrence and progression of human cancers, and have thus provided emerging drug discovery opportunities [9][10][11][12]. In GC, several DUBs participate in tumor initiation and progression.…”
Section: Ivyspring International Publishermentioning
confidence: 94%
“…According to previously described protocols, we used forty samples containing both HCC and adjacent nontumor tissues for the immunohistochemical staining with anti-UBE2O antibody (1:200, 15812-1-AP, Proteintech, Wuhan, China) 22 . Two pathologists examined the slides in a double-blind fashion.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, increasing DUBs were identified as tumor promoters via deubiquitinating and stabilizing certain oncoproteins in cancers, and were proposed as novel therapeutic targets. In this study, we showed that ARV-771 can downregulate multiple DUBs in HCC, including USP1, USP8, USP10, USP13, and USP18, which have been implicated in the tumorigenesis and progression by regulating certain substrates ( Cai et al, 2017 ; Gao et al, 2020 ; Zhu et al, 2020 ; Liao et al, 2021b ; Zhu et al, 2021 ). Therefore, we hypothesized that the reduction of USP1, USP8, USP10, USP13, and USP18 may all involve in the ARV-771-induced growth inhibition in HCC.…”
Section: Disccussionmentioning
confidence: 80%